Carbazole-based D-π-A molecules: Determining the photophysical properties and comparing ICT effects of π-spacer and acceptor groups - Altınölçek, Nuray; Battal, Ahmet; Vardalli, Cemre Nur; Tavasli, Mustafa; Yu, Holly A.; Peveler, William J.; Skabara, Peter J. (Elsevier B.V., 2021)
4-(9′-Hexylcarbazol-3′-yl)benzaldehyde (Cz-Ph-CHO: 4) and 4-(9′-hexylcarbazol-3′-yl)benzylidenemalononitrile (Cz-Ph-CN: 5) were synthesised with the structure of D-π-A, where carbazole, phenylene and formyl/dicyanovinyl groups act as electron donor (D), pi-spacer (π) and electron acceptor (A) units, respectively. The thermal, electrochemical, optical and intramolecular charge transfer (ICT) properties of compounds 4 and 5 were investigated. Compounds 4 and 5, in particular their ICT behaviour, were also compared with the closely related structure, 2-(9′-hexylcarbazol-3′-yl)-5-pyridinecarbaldehyde (Cz-Py-CHO: 7). For the purpose of tuning chemical structure to obtain targeted properties, electrochemical data and absorption and emission measurements suggest that the dicyanovinyl unit in compound 5 is a better acceptor than formyl in compound 4, and that pyridine in compound 7 is a better π-spacer than benzene in compound 4, in exerting ICT characteristics such as fluorosolvatochromism and Stokes shifts. © 2021 Elsevier B.V.
Keywords: Acceptor; Carbazole; Intramolecular charge transfer; Solvatochromism; Stokes shiftπ; spacers